Pendidikan Islam di Masjid Kampus; Perbandingan Majlis Ta’lim di Masjid Kampus Yogyakarta - Habibi, Moh Mizan; Moh. Mizan Habibi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
This research is an effort in developing study in Islamic education toward the wider area, especially by touching the implementation of Islamic education outside mainstream educational activities –Madrasah, Islamic Boarding School, and Islamic HigherEducation- When Islamic education is defined as a learning process based on Islamic values, the logical consequence is that the discussion of its actualization should convey the whole educational process framed by Islamic system and values. Majlis ta’lim activity in university-based mosques in Yogyakarta (Sunan Kalijaga Mosque, UGM Mosque, and KH Ahmad Dahlan Mosque in UMY) made by the researcher as a research object, because of their part in Islamic education application form and their existence under a university as a base of wide scientific development.